Trouble with Hubble: Status of the Big Bang Models. Issue 5 (25th December 2022) - Smeenk, Chris
Abstract: Cosmologists take the Λ CDM model to be a permanent contribution to our knowledge of the universe, based on the success of precision cosmology. Consistent, independent determinations of the parameters in this model encourage physicists to take it seriously. This stance incurs an obligation to resolve any discrepancies by reanalyzing measurements or adding further complexity. Recent observations in cosmology indicate a tension between "local" and "global" determinations of the Hubble constant. Here I argue that this tension illustrates one of the benefits of taking the model seriously and consider the challenges to making a case for the permanence of Λ CDM.